Recognizing European cancer nursing: protocol for a systematic review and meta-analysis of the evidence of effectiveness and value of cancer nursing - Campbell, Pauline; Torrens, Claire; Kelly, Daniel; Charalambous, Andreas; Domenech-Climent, Nuria; Nohavova, Iveta; Östlund, Ulrika; Patiraki, Elisabeth; Salisbury, David; Sharp, Lena; Wiseman, Theresa; Oldenmenger, Wendy; et al. (My University, 2017)
Aim: To identify, appraise and synthesize the available evidence relating to the value and impact of cancer nursing on patient experience and outcomes. Background: There is a growing body of literature that recognizes the importance and contribution of cancer nurses, however, a comprehensive review examining how cancer nurses have an impact on care quality, patient outcomes and overall experience of cancer, as well as cost of services across the entire cancer spectrum is lacking. Design: A systematic review and meta-analysis using Cochrane methods. Methods: We will systematically search 10 electronic databases from 2000, with pre-determined search terms. No language restrictions will be applied. We will include all randomized and controlled before-and-after studies that compare cancer nursing interventions to a standard care or no intervention. Two reviewers will independently assess the eligibility of the studies and appraise methodological quality using the Cochrane Risk of Bias tool. Disagreements will be resolved by discussion and may involve a third reviewer if necessary. Data from included studies will be extracted in accordance with the Template for intervention Description and Replication reporting guidelines. Missing data will be actively sought from all trialists. Data will be synthesized in evidence tables and narrative to answer three key questions. If sufficient data are available, we will perform meta-analyses. Discussion: This review will allow us to systematically assess the impact of cancer nursing on patient care and experience. This evidence will be used to determine implications for clinical practice and used to inform future programme and policy decisions in Europe.
Keywords: Cancer; Cost; Effectiveness; Nurse-led; Nursing; Oncology PROMS; Patient care